(untitled) (Світ фінансів, 2017)
Кравчук Н. Я. Модифікація ринку фінансових послуг крізь призму фінансової консолідації: функціональна детермінованість та діалектика пізнання. Розкрито сутність, форми та методи фінансової консолідації. Систематизовано ключові детермінанти процесу фінансової консолідації; на основі аналізу причинно-наслідкових залеж- ностей явищ глобалізації та фінансової консолідації доведено, що остання є потужним каталізатором глобального розвитку. Висвітлено неоднозначний вплив фінансової консолідації на модифікацію ринку фінансових послуг в умовах глобалізації, акцентовано увагу на проблемах формування нової світової фінансової архітектури. Kravchuk N. Modification of financial services market in the light of financial consolidation: functional determination and dialectics of cognition. The essence, forms and methods of financial consolidation are described. The key determinants of financial consolidation process are systematized. Analysing dependence of cause and effect of globalization phenomena and financial consolidation, it is proved that the latter is the powerful catalyst of global development. Ambiguous influence of financial consolidation on financial services market modification within globalization is considered. The problems of new world financial architecture forming are emphasized on.